PENGEMBANGAN POTENSI DAN PROMOSI DESA LOYOK SEBAGAI DESA WISATA - Ramdhani, Eka Putri Cahya; Hanafi, Muhammad; Hakiki, Dina; Demastita, Ni Putu Fanty; Mohammad, Amrija; Usniati, Ita; Nindiyana, Baiq Nurmaulida; Syufina, Arina Shofia; Mau’ud, Mohamad; Auliya, Isnie; Marzuki, Marzuki (Jurnal Wicara, 2023)
KKN means practicing knowledge received in college directly in the midst of society (Big Indonesian Dictionary). In the Mataram University KKN-Thematic activities carried out in Loyok Village, Sikur District, East Lombok Regency, the Mataram University KKN-Thematic group and Mataram University Lecturers carried out various activities with the main target of the activity namely developing the tourism potential of Loyok Village. The purpose of implementing the KKN-Thematic University of Mataram is to answer various problems that exist in the social community, including in agriculture, social affairs, education and tourism. Based on the survey results and discussions with village officials regarding the situation in Loyok Village, Mataram University KKN-Thematic Students designed various activities such as clearing signposts and maps of tourist destinations and making promotional videos. The results of the activities carried out during the KKN-Thematic work period at the University of Mataram are signposts and maps of tourist destinations that can help tourists find the location of Loyok Village as well as promotional videos for tourist villages that can introduce tourist destinations in Loyok Village. In addition, Mataram University KKN-T students are also involved in various other activities, namely socialization on prevention of early marriage, teaching at school, teaching the Koran, making compost, planting seeds, and clean Friday. The results of the activities carried out can improve good relations between the community and Mataram University KKN-Thematic Students.